2011
DOI: 10.1158/1078-0432.ccr-10-1745
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib Enhances the Efficacy of Fulvestrant by Amplifying the Aggregation of the Estrogen Receptor, Which Leads to a Proapoptotic Unfolded Protein Response

Abstract: Purpose Fulvestrant is known to promote the degradation of the estrogen receptor (ER) in the nucleus. However, fulvestrant also promotes the aggregation of the newly synthesized ER in the cytoplasm. Accumulation of protein aggregates leads to cell death but this effect is limited as a result of their elimination by the proteasome. We tested whether combining fulvestrant with the proteasome inhibitor, bortezomib, could enhance the accumulation of ER aggregates and cause apoptotic cell death. Experimental Desi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 27 publications
4
28
3
Order By: Relevance
“…A recent study reported a combinatorial effect of fulvestrant and bortezomib on the induction of apoptosis and laid the ground work for ongoing clinical trials combining these 2 treatments (16). In this study, we were unable to see any effects of bortezomib treatment on the rapid fulvestrantinduced ERa downregulation and the repression of ERa target gene transcription or ERa binding.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…A recent study reported a combinatorial effect of fulvestrant and bortezomib on the induction of apoptosis and laid the ground work for ongoing clinical trials combining these 2 treatments (16). In this study, we were unable to see any effects of bortezomib treatment on the rapid fulvestrantinduced ERa downregulation and the repression of ERa target gene transcription or ERa binding.…”
Section: Discussioncontrasting
confidence: 62%
“…S1C). Surprisingly, in contrast to previous reports (16,26), whereas bortezomib effectively decreased estrogen-induced proteasomal degradation of ERa ( Supplementary Fig. S1D) in a manner similar to that reported for MG132 (9, 27), we observed little or no effect of bortezomib on fulvestrant-induced ERa downregulation ( Supplementary Fig.…”
Section: Bortezomib Blocks Proteasome Activity In Mcf7 Breast Cancer contrasting
confidence: 55%
See 1 more Smart Citation
“…9 Moreover, cytosolic accumulation of ER was previously shown to induce the endoplasmic reticulum stress pathway, the unfolded protein response (UPR) that might link IRF1/ERa/UPR signaling. 10 A pathway schematic illustrating the IRF1/ERa/ATG7 signaling axis is shown in Figure 1. Interestingly, neither the chemical inhibitors HCQ and 3-methyladenine (3-MA) nor treatment with ATG5 siRNA resulted in elevated IRF1 levels in the ERC breast cancer cell lines, suggesting that this relationship is directly mediated by ATG7 or BECN1 protein signaling and not by autophagic flux.…”
Section: Linking Irf1 and Autophagymentioning
confidence: 99%
“…The clinical data to show that these conditions have been consistently exacerbated or ameliorated under conditions of altered sex hormonal levels is also lacking. [26][27][28][29] Lyonization The most obvious gender-specific differences among monogenic disorders are the differences in prevalence, onset, and severity of clinical manifestations of X-linked inherited conditions. One mechanism that contributes to this variability is X-Chromosomal inactivation (lyonization).…”
Section: Unfolded Protein Responsementioning
confidence: 99%